2021
DOI: 10.1002/adma.202105789
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Metal‐Enabled Mechanical‐Energy‐Induced CO2 Conversion

Abstract: (10 of 11)www.advmat.de www.advancedsciencenews.com steps in the pre-edge region of the XAS spectra (10 167-10 347 eV), 0.25 eV steps in the XANES region (10 347-10 417 eV). In the extended X-ray absorption fine structure region spectra were collected, in steps of 0.035k to a maximum of 10k, with count time increasing linearly from 2 up to 4 s at the end of the energy range. Multiple scans were collected for each sample. Data were preprocessed using Sakura (in-house program) and the Athena program for scan ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 40 publications
(57 reference statements)
1
89
0
Order By: Relevance
“…The results presented here offer new insights that the ultrasonic high-energy hot spots create a chemical reaction field at the liquid metal/solution interface for promoting thermally metal-catalyzed reactions. The ultrasonically-activated EGaIn liquid metals would also encourage further research on thermal catalytic conversions such as CO 2 41 and CH 4 . 42 This work was financially supported by the JSPS KAKENHI under Grant No.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The results presented here offer new insights that the ultrasonic high-energy hot spots create a chemical reaction field at the liquid metal/solution interface for promoting thermally metal-catalyzed reactions. The ultrasonically-activated EGaIn liquid metals would also encourage further research on thermal catalytic conversions such as CO 2 41 and CH 4 . 42 This work was financially supported by the JSPS KAKENHI under Grant No.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…[192] Just recently, liquid metal has been proposed as a component for the reduction of CO 2 into carbonaceous solid products and O 2 , providing a green technology for the treatment of CO 2 emissions. [193]…”
Section: Soft Electronics Soft Robots As Well As Reaction Environmentmentioning
confidence: 99%
“…Similarly, in polymerization reactions, the liquid metal was found to promote the polymerization, rendering the removal of oxygen for certain polymerization processes obsolete [192] . Just recently, liquid metal has been proposed as a component for the reduction of CO 2 into carbonaceous solid products and O 2 , providing a green technology for the treatment of CO 2 emissions [193] …”
Section: A Brief Historymentioning
confidence: 99%
“…This comparison indicates that In 3 Sn is the most active component of our catalyst for the NO 3 RR. Another advantage of using liquid metals is that the surface does not easily foul as demonstrated by recent studies on electrochemical and sonochemical reduction of CO 2 to solid carbon [12,15] which does not stick to the surface due to the lack of van der Waals adhesion on the liquid surface which may aid with desorption processes.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Liquid metals have recently emerged as promising materials that are highly active for both catalysis and electrocatalysis. For the former, liquid metal based materials have been employed for quite difficult reactions such as the catalytic reduction of CO 2 to solid carbon under both room temperature [12] and elevated temperature conditions [13] and the sonocatalytic reduction of organic dyes to solid carbon [14] indicating the excellent catalytic properties of these materials. Previous electrocatalytic studies have indicated that Ga based liquid metal composites can also electrochemically reduce CO 2 to solid carbon.…”
mentioning
confidence: 99%